The Role of High Concentration of Resistin in Endothelial Dysfunction Through Induction of Proinflammatory Cytokines Tumor Necrosis Factor-alpha (TNF-alpha), Interleukin-6 (IL-6) and Chemokin Monocyte Chemotactic Protein-1 (MCP-1) - Anna Meiliana; Ilhamjaya Patellongi; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2009)
BACKGROUND: Many previous studies have reported that central obesity is related to inflammation and endothelial dysfunction. It has also been reported that resistin can induce proinflammatory cytokines TNF-α and IL-6, which can result in endothelial dysfunction, although the role of resistin in human remains unclear. The aim of this study was to assess the role of resistin in influencing the proinflammatory cytokines TNF-α, IL-6, and chemokin MCP-1 in nondiabetic, central obese individuals. Results of this study are hoped to be useful to make a strategy for early prevention of endothelial dysfunction especially in obese individuals.METHOD: This was a cross-sectional study on 73 non diabetic obese male subjects (waist circumferences >90 cm). Resistin, hs-TNF-α, IL-6, MCP-1, VCAM-1 were assessed by ELISA. Statistical analysis was performed using SPSS for Windows v.11.5 with significance p<0.05. The correlations among biomarkers were assessed using Spearman’s Rho test.RESULTS: The study results showed a significant correlation between resistin and TNF-α (r=0.274, p<0.005), and a significant correlation between TNF-α and IL-6 (r=0.430, p<0.001). It was found that high concentration of resistin caused the concentration of TNF-α , IL-6 and MCP-1 to increase, and affected the increase of VCAM-1 (p=0.0030), A significant correlation between waist circumference and inflammation (hsCRP, r=0.296, p<0.005; IL-6, r=0.374, p<0.001 and HOMA IR, r=0.331, p<0.001) was also found.CONCLUSION: This study showed that the role of resistin in endothelial dysfunction occurred at a high concentration of resistin through induction of proinflammatory cytokines TNF-α, IL-6, and chemokin MCP-1. We suggest that inflammation in obesity starts with a positive feedback loop mechanism between resistin and TNF-α.KEYWORDS: obesity, inflammation, adipocytokines, resistin, tumor necrosis factor-α, interleukin-6, monocyte chemotactic protein-1, vascular cell adhesion molecule–1